Three-point correlation bounds on the effective bulk modulus of isotropic multicomponent materials - Chinh, Pham Duc; Dong, Vu Lam (Vietnam Journal of Mechanics, 2012)
Three-point correlation bounds based on minimum energy principles are constructed to give estimates on the effective elastic bulk modulus of disordered multi-component materials. The constructed trial fields are extensions of Hashin-Shtrikman polarization ones used in our previous approach and lead to tighter bounds. Some examples of applications are presented.